The Role of Mitochondrial Dynamics and Mitotic Fission in Regulating the Cell Cycle in Cancer and Pulmonary Arterial Hypertension: Implications for Dynamin-Related Protein 1 and Mitofusin2 in Hyperproliferative Diseases - Pierce Colpman; Asish Dasgupta; Stephen L. Archer (Cells, 2023)
Mitochondria, which generate ATP through aerobic respiration, also have important noncanonical functions. Mitochondria are dynamic organelles, that engage in fission (division), fusion (joining) and translocation. They also regulate intracellular calcium homeostasis, serve as oxygen-sensors, regulate inflammation, participate in cellular and organellar quality control and regulate the cell cycle. Mitochondrial fission is mediated by the large GTPase, dynamin-related protein 1 (Drp1) which, when activated, translocates to the outer mitochondrial membrane (OMM) where it interacts with binding proteins (Fis1, MFF, MiD49 and MiD51). At a site demarcated by the endoplasmic reticulum, fission proteins create a macromolecular ring that divides the organelle. The functional consequence of fission is contextual. Physiological fission in healthy, nonproliferating cells mediates organellar quality control, eliminating dysfunctional portions of the mitochondria via mitophagy. Pathological fission in somatic cells generates reactive oxygen species and triggers cell death. In dividing cells, Drp1-mediated mitotic fission is critical to cell cycle progression, ensuring that daughter cells receive equitable distribution of mitochondria. Mitochondrial fusion is regulated by the large GTPases mitofusin-1 (Mfn1) and mitofusin-2 (Mfn2), which fuse the OMM, and optic atrophy 1 (OPA-1), which fuses the inner mitochondrial membrane. Mitochondrial fusion mediates complementation, an important mitochondrial quality control mechanism. Fusion also favors oxidative metabolism, intracellular calcium homeostasis and inhibits cell proliferation. Mitochondrial lipids, cardiolipin and phosphatidic acid, also regulate fission and fusion, respectively. Here we review the role of mitochondrial dynamics in health and disease and discuss emerging concepts in the field, such as the role of central versus peripheral fission and the potential role of dynamin 2 (DNM2) as a fission mediator. In hyperproliferative diseases, such as pulmonary arterial hypertension and cancer, Drp1 and its binding partners are upregulated and activated, positing mitochondrial fission as an emerging therapeutic target.